Management Process Intervention to Improve the Performance of MSMEs in the Food Processing Sector (Study on CV Cucuruku Ceria) - Nuzulla, Rifemi Ihza; Noer, Irmayani; Syahpura, Suraya Kaffi; Hidayat, Beni (Journal of International Conference Proceedings, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's food sector play a strategic role in economic development through employment, community empowerment, and food supply. However, food safety remains a major challenge due to profit-oriented practices, limited knowledge, weak supervision, and financial constraints. This study aims to examine the implementation of Good Manufacturing Practice (GMP) as a management intervention to improve MSME performance, competitiveness, and sustainability. The research was conducted over four months on a developing MSME in Lampung, Indonesia CV Cucurutuku Ceria which received support from the Netherlands-based Programma Uitzending Managers (PUM). GMP evaluation referred to Ministry of Industry Regulation No. 75 of 2010, starting with an initial assessment followed by consistency monitoring. Barriers to implementation were analyzed using the root cause analysis method, specifically the why-why technique. The results show that GMP compliance increased from 66% to 98% within three months, supported by management commitment, external funding, and problem-solving strategies. This study concludes that GMP can be effectively implemented in MSMEs with structured guidance, external collaboration, and consistent evaluation, contributing to improved food safety standards and business sustainability.